TRADISI PENGUBURAN DALAM GUA DAN CERUK PADA MASYARAKAT WEB DI KAMPUNG YURUF DISTRIK WEB KABUPATEN KEEROM - Fairyo, Klementin (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2012)
Burial in caves and niches on the Web is a prehistoric tradition continues. The tradition has been entrenched so that people in the process of implementation of the burial sites in caves and niches, often perform ritual dances accompanied by traditional feast. Archaeological evidence of burial traditions in the caves and niches are the archaeological remains in the form of human skulls, container crates, and the provision of the grave in the form of a dinner plate, bowl to drink, where betel lime, necklaces, camshaft, arrows, dogs and skull cow skull. Burial site in the caves and niches in Kampung District Yuruf Web can be encountered on how the site is the burial cave caves Yadumblu, Jigiyaw niche, niche Gumumblu 2, and complex cave site Yanglebi comprising caves, alcoves and cliffs.